Evaluation of Demographic Data, Clinical and Laboratory Findings, and Treatments Administered to Children Followed Up with a Diagnosis of Chronic Hepatitis B Infection - Deveci, Ugur; Dogan, Yasar; Kayaokay, Abdullah Murat; Akgeyik, Sukran; Karakoc, Ferhat; Hayirlidag, Mustafa (Galenos Publ House, 2024)
Objectives: This study examined the demographic and clinical features of children who were followed up with a diagnosis of chronic hepatitis B virus (HBV) infection. Materials and Methods: The study included 374 children who were followed up with a diagnosis of chronic HBV infection in our clinic between 2005 and 2023. Results: The study included 249 (66.6%) males and 125 (33.4%) females. The frequency of chronic HBV infection seen in the siblings of females with chronic HBV infection was determined to be significantly higher than that in male patients (p=0.017). Chronic active hepatitis was present in 147 (39.3%) patients. The route of infection was perinatal in all cases. Of the study cases, 79% were born in or before 2003 and 20% were born after 2003. The treatments administered to the cases were tenofovir disoproxil fumarate in 61 cases, lamivudine in 54, interferon 2 alpha in 53, and entecavir in 10. The frequency of active chronic HBV infection was significantly higher in children born in or after 2006 (p=0.036). Similarly, the incidence of inflammation was significantly higher in those born in 2006 and later (p=0.049). The rate of anti-hepatitis A virus immunoglobulin G positivity was statistically significantly higher in children born between 2003 and 2006 than in other age groups (p=0.003). Conclusion: Family members of these children should be screened for HBV infection. Because of studies in T & uuml;rkiye in recent years, there has been a significant decrease in the frequency of HBV infection in children.
Kronik Hepatit B Enfeksiyonu Tanısıyla izlenen Çocukların Demografik, Klinik ve Laboratuvar Bulguları ile Birlikte Aldıkları Tedavilerin Değerlendirmesi
Keywords: Children; hepatitis B virus; infection; vaccination